Program Edukasi Keseimbangan Tubuh Untuk Masyarakat Menjaga Kesehatan dan Mencegah Cidera - Astrid Komala Dewi; Catherine Hermawan Salim; Yurita Mailintina; Ria Efkelin (Lembaga Pengembangan Kinerja Dosen, 2025)
Purpose: This Community Service is to Increase Public Knowledge and Provide an understanding to the public about the importance of body balance as one of the pillars of optimal physical health. As well as Encouraging Healthy Living Behavior and Educating the public about ways to maintain and train body balance through appropriate and safe physical activities. And Prevention of Injury Risk Reducing the risk of falls and injuries, especially in vulnerable groups such as the elderly, by increasing awareness and ability to maintain posture and body stability. As well as Improving the Quality of Life of the community Helping to achieve a better quality of life through effective and independent management of body functions. The sample consisted of 30 people and was selected based on a random sampling technique using the available questionnaire. The sample was measured using the Sitting Balance measurement to assess its Balance Level. Method: This Community Service is a pre-post test design. Of the 30 Respondents who obtained an N-Gain Score of 72.5, it showed that the method applied by the researcher in this activity was effective. In addition, the distribution of the N-Gain Score with a value of 0.9 indicates that this strength or category is at a high level